Analisis Pengaturan Apron oleh Petugas Apron Movement Control (AMC) dalam Menunjang Pelayanan dan Keselamatan Penerbangan di Bandar Udara Tunggal Wulung Cilacap - Muamar Sabilul muttaqin (Jurnal Multidisiplin Madani, 2022)
The implementation of control of the movement of aircraft, vehicles and on the apron must be monitored by the relevant Apron Movement Control (AMC) officers in maintaining and improving the security and traffic safety of the movement of aircraft, vehicles and people, so as to create aspects of security, safety and smoothness on the air side. especially on the apron. This study aims to determine the provision of safety for personnel, vehicles and equipment while on the apron because there is no service road, and to determine the parking arrangements for pilot school aircraft by Apron Movement Control (AMC) officers. The study used qualitative research methods, using the Triangulation method. The results showed that 1) Aviation safety on the air side is the most important part in the implementation of flight activities, 2) Training aircraft parking is carried out by training instructors from each pilot school and has been determined by AMC officers. If there are additional aircraft, there will be a change in the parking system, where the AMC unit plays a role in taking over the task of parking the aircraft.